Creating competitive advantage : Maruti Suzuki India Ltd. - Salwan, Prashant (London : NeilsonJournals Publishing, 2017)
Maruti Suzuki India Ltd. (MSIL) is India's largest car manufacturer and leading distributor of spare parts, dealing primarily in passenger vehicles, multi-utility, and multi-purpose vehicles. It has an extensive network of sales outlets across the country. MSIL went through three distinct phases: up to 1999 the market was a sellers market and there was very little competition; post 2000 (first recession) till 2007 when other multinationals entered the Indian market and customers began looking for design safety; and post the 2008–09 global financial crisis (second recession). In the second phase MSIL created value through cost leadership strategies, design and new product launches. MSIL managed to create value under growing competition from 2004 to 2008. At the beginning of FY 2007–2008 MSIL had attained a growth rate of 12%, slightly higher than the industry average, but during FY 2008–09, the sales volumes dropped resulting in a net profit slow down of 29.6%. S. Nakanishi (MSIL's MD and CEO) faced a serious challenge: how to maintain competitiveness while dealing with growing domestic demand and changing customer preferences.
Originally Published InSalwan, P. (2017). Creating competitive advantage: Maruti Suzuki India Ltd. Journal of International Business Education, 12(1), 353–374. JIBE12-0CS6.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Competition -- India; Automobile industry and trade -- India